Church of the Resurrection at Ulukhaktok, NT - Farnel, Sharon (2017)
The Church of the Resurrection at Ulukhaktok, NT on Victoria Island at 70°43°N and 117°45°W. Ulukhaktok is one of the six largest communities in the Inuvialuit Settlement Region. This Anglican Church serves a population of about 400 (2016).